Pyrazolopyridine Ligands in Transition-Metal-Catalyzed C–C and C–Heteroatom Bond-Forming Reactions - Kang, Eunsu; Joo, Jung Min (Synthesis, 2023)
Pyrazole-substituted pyridines have emerged as versatile bidentate ligands in transition-metal catalysis, providing opportunities to fine-tune reactivity and selectivity beyond what conventional bipyridine ligands can achieve. This review focuses on two representative pyrazolopyridine ligands: 2-(1H-pyrazol-1-yl)pyridine (1-PzPy) and 2-(1H-pyrazol-3-yl)pyridine (3-PzPy). The 1-PzPy series, characterized by a pyrazole ring serving as a weakly coordinating Lewis basic ligand, offer flexibility in ligand binding. Alternatively, the 3-PzPy series provide both L2- and LX-type binding modes, functioning as hydrogen bond donors and σ-donors, respectively. The structural diversity of pyrazolopyridine ligands enables the development of various synthetic strategies, facilitating cross-coupling, cycloaddition, photocatalytic, and asymmetric reactions. This review highlights the roles of these ligands in advancing transition-metal-catalyzed C–C and C–heteroatom bond-forming reactions.1 Introduction2 Synthesis of Pyrazolopyridine Ligands3 Applications of 1-PzPy Ligands4 Applications of 3-PzPy Ligands5 Conclusion
Keywords: ligands; pyrazoles; pyridines; bidentate; C–H activation; palladium; photocatalysis; asymmetric catalysis